Performance of a Score to Characterize Adequate Contact among the Social Network of Persons with Tuberculosis - Castellanos, Maria Eugenia; Zalwango, Sarah; Quach, Trang; Kakaire, Robert; Martínez, Leonardo; Ebell, Mark H.; Dobbin, Kevin K.; Kiwanuka, Noah; Whalen, Christopher C. (Research Square, 2021)
Exposure to an individual with tuberculosis is necessary for transmission to occur. Previously, we developed a score that measures contact between tuberculosis cases and their social networks in an African urban context. This score was built using exploratory factor analysis and identified contact as the conjunction of two domains – setting and relationship. Now, our aim is to determine whether this score covaries with the presence of tuberculous infection among social contacts of tuberculosis cases.
Keywords: Tuberculous infection; Tuberculosis; Contact; Transmission; Social network